Pedicled Flaps for High-Risk Open Vascular Procedures of the Lower Extremity: An Analysis of The National Surgical Quality Improvement Project Database - Garvey, Shannon R.; Valentine, Lauren; Weidman, Allan A.; Chen, Amy; Nanda, Asha D.; Lee, Daniela; Lin, Samuel J.; Lee, Bernard T.; Liang, Patric; Cauley, Ryan P. (Journal of Reconstructive Microsurgery, 2023)
Background Use of pedicled flaps in vascular procedures is associated with decreased infection and wound breakdown. We evaluated the risk profile and postoperative complications associated with lower extremity open vascular procedures with and without pedicled flaps.Methods The American College of Surgeons National Surgical Quality Improvement Program database (2010–2020) was queried for Current Procedural Terminology codes representing lower extremity open vascular procedures, including trunk and lower extremity pedicled flaps. Flap patients were compared with a randomized control group without flaps (1:3 cases to controls). Univariate and multivariate analyses were performed.Results We identified 132,934 adults who underwent lower extremity open vascular procedures. Concurrent pedicled flaps were rare (0.7%), and patients undergoing bypass procedures were more likely to receive a flap than nonbypass patients (69 vs. 64%, p < 0.0001). Flap patients had greater comorbidities. On univariate analysis, flap patients were more likely to experience wound (p = 0.0026), mild systemic (p < 0.0001), severe systemic (p = 0.0452), and all-cause complications (p < 0.0001). After adjusting for factors clinically suspected to be associated with increased risk (gender, body mass index, procedure type, American Society of Anesthesiologists classification, functional status, diabetes, smoking, and albumin < 3.5 mg/dL), wound (p = 0.096) and severe systemic complications (p = 0.0719) were no longer significantly associated with flap patients.Conclusion Lower extremity vascular procedures are associated with a high risk of complications. Use of pedicled flaps remains uncommon and more often performed in patients with greater comorbid disease. However, after risk adjustment, use of a pedicled flap in high-risk patients may be associated with lower than expected wound and severe systemic complications.
Keywords: prophylactic plastic surgery; prophylactic muscle flap; high-risk vascular surgery